Spatial analysis of Archaeological and historical sites and their relationship with the Natural and Human Factors case study: Al Baha region - Alahmari, Ashwag Said; Ouerghi, Sarra Al-Habib (Journal of natural sciences, life and applied sciences, 2020)
This paper aims to identify the archaeological and historical sites, the geographical distribution, and the spatial relations between them and other geographical phenomena in Al-Baha, which provides us with a comprehensive view of the current status of these archaeological and historical sites and developing awareness of its importance as tourist sites. To achieve the research goals, to achieve research objectives, the spatial analysis approach in the GIS environment was used to measure spatial geographical phenomena in the study area through its statistical and spatial analysis tools. The cartographic presentation and mapping method was adopted using the GIS software 10.6. The study concluded that the number of archaeological and historical sites in Al-Baha has reached about 129 sites distributed among 7 governorates. Its relative distribution was very different between the western and eastern parts of the region (about 97 archaeological and historical sites in east and 32 archaeological and historical sites west, with 75% of sites in the east and 25% of sites in the west) in close association with topography, water resources, mineral resources and historic trade routes. The distribution of archaeological and historical sites in the area of Al-Baha was a close distribution in its entirety (Neighborhood Index=0.63) due to the limitation and small areas of plains that are suitable for settlement and the proliferation of the steep highlands and vast desert over the area of Al-Baha. The density of archaeological and historical sites was high in the eastern part and fell in the western part of the study area. The study recommended the importance of using GIS applications to study the spatial distribution of archaeological and historical sites and the spatial relations between them and the various natural and human phenomena in the study area. Using the spatial analysis output to prepare archaeological atlas containing maps, illustrations and photographs of the archaeological and historical sites in the region for the purpose of exploiting and commercializing these potential resources. Also, encouraging studies and research that contribute to highlighting the importance of archaeological and historical sites and encouraging exploiting them in several special fields, including tourism.